Biosynthesis of 2-acetyl-1-pyrroline in rice calli cultures: Demonstration of 1-pyrroline as a limiting substrate. (15th April 2016) - Poonlaphdecha, Janchai; Gantet, Pascal; Maraval, Isabelle; Sauvage, François-Xavier; Menut, Chantal; Morère, Alain; Boulanger, Renaud; Wüst, Matthias; Gunata, Ziya
Highlights: 1-Pyrroline is a limiting factor in the formation of 2-acetyl-1-pyrroline, key flavour compound in fragrant rice. When 1-pyrroline is available in non-fragrant rice, the level of 2-acetyl-1-pyrroline may reach that of fragrant rice. Acetylation of 1-pyrroline ring seems not to be a limiting factor in the formation of 2-acetyl-1-pyrroline. Thanks to labelling experiments, acetyl CoA was proposed as a good candidate for acetylation of the 1-pyrroline ring. Abstract: The role of 1-pyrroline was studied via feeding experiments using rice calli cultures to gain further insight into the key steps of 2-acetyl-1-pyrroline (2AP) biosynthesis in rice. The origin of the acetyl donor was also studied through stable isotope labelled substrates. Incubation of fresh calli from a fragrant rice variety (Aychade) and a non-fragrant variety (Gladio × Fidji K2) with 1-pyrroline led to a significant increase in 2AP in both varieties. Importantly, the amount of 2AP in the non-fragrant variety could be greatly enhanced by this supplementation. When rice calli were fed with increasing levels of 1-pyrroline, 2AP levels increased accordingly. Our data show that 1-pyrroline is a limiting factor for 2AP synthesis in rice. Heat treatment of calli suggested that 1-pyrroline might be enzymatically acetylated. The presence of labelled 2AP in calli supplemented with [U- 13 C]glucose, sodium acetate (1, 2- 13 C2 ) and sodium octanoate (1, 2, 3, 4- 13 C4 ) suggested that these compounds are possible candidates for acetyl group-donors of 2AP, predominately in the form of intact labelled 13 C2 -units.